Understanding the impact of gendered roles on the experiences of infertility amongst men and women in Punjab - Mumtaz Zubia; Shahid Umber; Levay Adrienne (BMC, 2013)
Abstract While infertility is a global challenge for millions of couples, low income countries have particularly high rates, of up to 30%. Infertility in these contexts is not limited to its clinical definition but is a socially constructed notion with varying definitions. In highly pronatalistic and patriarchal societies like Pakistan, women bear the brunt of the social, emotional and physical consequences of childlessness. While the often harsh consequences of childlessness for Pakistani women have been widely documented, there is a dearth of exploration into the ways in which prescribed gender roles inform the experiences of childlessness among Pakistani women and men. The aim of this study was to explore and compare how gender ideologies, values and expectations shape women's and men's experiences of infertility in Pakistan. Using an interpretive descriptive approach, in-depth interviews were conducted with 12 women and 8 men experiencing childlessness in Punjab, Pakistan from April to May 2008. Data analysis was thematic and inductive based on the principles of content analysis. The experience of infertility for men and women is largely determined by their prescribed gender roles. Childlessness weakened marital bonds with gendered consequences. For women, motherhood is not only a source of status and power, it is the only avenue for women to ensure their marital security. Weak marital ties did not affect men's social identity, security or power. Women also face harsher psychosocial, social, emotional and physical consequences of childlessness than men. They experienced abuse, exclusion and stigmatization at the couple, household and societal level, while men only experienced minor taunting from friends. Women unceasingly sought invasive infertility treatments, while most men assumed there was nothing wrong with themselves. This study highlights the ways in which gender roles and norms shape the experiences associated with involuntary childlessness for men and women in Punjab, Pakistan. The insight obtained into the range of experiences can potentially contribute to deeper understanding of the social construction of infertility and childlessness in pronatalistic and patriarchal societies as well as the ways in which gender ideologies operationalise to marginalise women.